Synaptic thermoprotection in a desert-dwelling Drosophila species. - Newman, A.E.; Xiao, C.; Robertson, R.M. (Journal of Neurobiology, 2005)
Synaptic transmission is a critical mechanism for transferring information from the nervous system to the body. Environmental stress, such as extreme temperature, can disrupt synaptic transmission and result in death. Previous work on larval Drosophila has shown that prior heat-shock exposure protects synaptic transmission against failure during subsequent thermal stress. This induced thermoprotection has been ascribed to an up-regulation of the inducible heat-shock protein, Hsp70. However, the mechanisms mediating natural thermoprotection in the wild are unknown. We compared synaptic thermosensitivity between D. melanogaster and a desert species, D. arizonae. Synaptic thermosensitivity and the functional limits of the related locomotor behavior differed significantly between closely related, albeit ecologically distinct species. Locomotory behavior of wandering third instar D. arizonae larvae was less thermosensitive and the upper temperature limit of locomotory function exceeded that of D. melanogaster by 6 degrees C. Behavioral results corresponded with significantly lower synaptic thermosensitivity at the neuromuscular junction in D. arizonae. Prior heat-shock protected only D. melanogaster by increasing relative excitatory junctional potential (EJP) duration, the time required for EJP failure at 40 degrees C, and the incidence of EJP recovery following heat-induced failure. Hsp70 induction profiles following heat-shock demonstrate up-regulation of inducible Hsp70 in D. melanogaster but not in D. arizonae. However, expression of Hsp70 under control conditions is greater in D. arizonae. These results suggest that the mechanisms of natural thermoprotection involve an increase in baseline Hsp70 expression.